2007
DOI: 10.3177/jnsv.53.489
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Liver Tyrosine Aminotransferase Increase in Ethanol-Treated Mice and Its Effect on Serum Tyrosine Level

Abstract: Summary Liver tyrosine aminotransferase (TAT) activity is known to increase with ethanol treatment; however, the mechanism of this increase is unclear. Upon investigation we found that TAT activity and mRNA levels started to increase 2 h after ethanol administration and continued to increase until 6 h after ethanol administration. The increase in ethanol-induced TAT activity could not be explained by calorie loading after fasting, since ethanol loading increased TAT expression, while glucose loading decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Total RNA was extracted using the acid guanidine thiocyanate-phenol-chloroform method [20]. Details of the northern hybridization method have been described previously [23].…”
Section: Rna Preparation and Hybridization Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted using the acid guanidine thiocyanate-phenol-chloroform method [20]. Details of the northern hybridization method have been described previously [23].…”
Section: Rna Preparation and Hybridization Analysismentioning
confidence: 99%
“…We previously reported that the non-specific adenosine receptor agonist 5'-N-ethylcarboxamide-adenosine (NECA) increased serum glucose levels and the expression of a glucogenic enzyme (glucose 6-phosphatase) in the liver [19] [20]. Based on the dose of NECA administered in these studies and plasma concentrations after the administration of other adenosine agonists [21], it was inferred that the serum NECA concentration was in the μM range and also that NECA activated adenosine A2b receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that in fasting mice treated with NECA for 6 h, serum glucose levels increased and serum alanine levels decreased [11]. Glucose is produced by the glucose-alanine cycle, and because serum alanine levels are decreased by NECA, it is thought that NECA stimulates gluconeogenesis.…”
Section: Introductionmentioning
confidence: 96%